HUBUNGAN SELF-EFFICACY DAN SELF-REGULATED LEARNING SISWA SMA KELAS XII - Sulaeman, Riemaya Martiza; Syamsuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The complexity of mathematics material at the high school level demands not only cognitive abilities but also support from affective and regulatory factors, particularly self-efficacy and self-regulated learning (SRL). This study employed a quantitative approach with a correlational design among a population of 12th-grade students at MAN 2 Jakarta, with a sample of 64 12th-grade students selected through purposive sampling based on their engagement in learning integral calculus material. Data were collected using a Likert-scale questionnaire that met high validity and reliability standards (Cronbach’s Alpha = 0.91). Spearman’s rank correlation analysis revealed a positive and significant relationship between self-efficacy and SRL (r = 0.577; p < 0.001). These results indicate that the higher students’ self-efficacy, the better their SRL skills in mathematics learning. These findings affirm the role of self-efficacy as an important psychological factor in supporting SRL, thus the strengthening of self-efficacy needs to be integrated into mathematics learning strategies at the high school level.